Amenaza de parto pretérmino en adolescente - Llanos Campozano, Jennifer Nataly (2021)
Preterm delivery is a multifactorial problem that continues to have an impact worldwide. The leading cause of neonatal morbidity and mortality in the world and its incidence has increased. Preterm labor is the process of birth between week 20 and 36.6 weeks of gestation. Every day there are prevalent data that preterm birth is a process of pathophysiological series, for which it has been studied and one of the updated advances is the fetal fibronectin test for the prevention of preterm birth in pregnant women with an index of low and high risk. For some years, the prevention of premature birth is based on an ultrasound control to evaluate the length of the cervix and thus estimate a good diagnosis in patients with this problem at risk of premature birth. Some preventive measures for a preterm delivery is the assistance of its prenatal control, the performance of its respective laboratory tests such as urinalysis, in order to find urinary tract infections, the non-consumption of toxic habits, and finally the supplementation of iron and zinc in women of low socioeconomic level.